EXPLORING TRAUMA AND HOPE IN REFUGEES’ POEMS - Emily Kui-Ling Lau; Nur Amalina Roslim; Nur Syasya Qistina Mazeree; Jia jin Tao (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2021)
A situation of enforced migration in which individuals are compelled to migrate against their own causes a sense of displacement (Shamsuddoha et al., 2012). As of 2019, UNHCR has confirmed a population of 79.5 million forcibly displaced refugees, which accounts for nearly one percent of the global population. Displaced refugees is a topic that has gained international focus in numerous disciplines - anthropography, geopolitics, health sciences, to name a few. This paper examines displaced refugees through two recent poems composed in 2018: Greetings to the People of Europe by Alemu Tebeje and When Exile Comes: How the Brain Reacts to Trauma by Eric Ngalle Charles. Both poets have lived as refugees, and they both have experienced displacement and consequently, its hardships. It aims to provide a linguistic lens in analysing displaced refugees’ plights by identifying and foregrounding distinctive linguistic devices in the poems.  The in-depth stylistic analysis of the poems unveils that, while trauma is commonly discovered, hope and future viewpoints are equally registered.